PAN Political Communication Strategy (Celebrities As Political Party Vote Getters In Legislative General Elections) - Deni kurniawan (Jurnal Ilmu Sosial dan Ilmu Politik, 2025)
The freedom of the people to participate in the democratic party is almost limitless. Likewise, political party cadres who run for the legislature, where almost all groups can run as legislative candidates. Not apart from celebrities, approaching the political year there are many celebrities who plunge into the world of politics. Regardless of the lack of jobs or just a sensation behind. Here researchers try to find the problem of celebrity trends entering into the cadres of the National Mandate Party. The author speculates that the participation of celebrities is one of the political communication strategies carried out by the National Mandate Party.celebrities is one of the political communication strategies carried out by PAN. In finding the results of this study, researchers used a qualitative approach by prioritizing literature studies sourced from articles, journals, and other media. Researchers in this case tried to find the problem of political communication strategies in one of the parties in Indonesia. And it was found that celebrity involvement is one of the strategies owned by PAN in increasing public participation in the upcoming elections.upcoming elections. Against the background of the declining level of vote acquisition each year of PAN.